Pelatihan Pengelolaan Arsip Berbasis Digital Bagi Remaja Masjid Baitul Halim (RBH) Mampang Prapatan Jakarta Selatan - Achmad Maezar Bayu Aji; Susy Rosida; Samudi; Yuni Eka Achyani; Dwi Cahyo Hadi Kusumo; Sukma Jaya; Dicky Taruna (Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
Community Service is a medium to bridge the world of education with society. Remaja Masjid Baitul Halim (RBH) Started as a gathering of Muslim youths, not only for spiritual interests but also as a place to exchange ideas to deal with problems that are being faced together. Information technology media is one of the media that helps a lot in the world of business or organizations, such as facilitating the processing and utilization of digital archives. This Community Service activity aims to improve the performance of the Remaja Masjid Baitul Halim, especially in the manufacture and management of the archives they have. This community service training introduces an application that has been made for archiving digital data that will be studied by Remaja Masjid Baitul Halim. The training was carried out by Lecturers and Students at Nusa Mandiri University. The main purpose of this community service is to train Remaja Masjid Baitul Halim to tidy up digital archive data.